Effects of media hype and mass popularity on essence of literature : as seen from J.K. Rowling's Harry Potter - Bakhtiar, Anita Zeba (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015